Towards a theology of the body. A spirituality of imperfection - Van Niekerk, Pieter (Nederduitse Gereformeerde Teologiese Tydskrif, 2013)
Human weakness, a disabled body, and fragile faith make a theology of vulnerability and finitude relevant. I was basically moulded in a theology which does not adequately address concrete daily life of vulnerable people who have disabilities. Traditionally theology does not deal with physical imperfection, decay and dying. Philosophies that separate the mind and body have a strong influence in Christian traditions. Dualism is antithetical to the reality of Christ who had a body himself. Henri Nouwen’s spiritual journey of vulnerability and brokenness make his “Spirituality of imperfection” grounded in experience. To come to accepting disease and death as part of life gives meaning to “we have this treasure in jars of clay”, according to 2 Cor 4:7.